Pengembangan Hukum Wakaf Produktif Untuk Mengatasi Kemiskinan Dan Ketergantungan - Aunur Rohim Faqih (Jurnal Hukum IUS QUIA IUSTUM, 2005)
To develop the economics of the society and to minimize poverty and interdependence, the management of property donated for religious use ( wakaf) productive can be exercised bymodem management anditis managed bytheprofessional people, trusted, productive and constantly basedon the Islamic values and the related regulations.